2005
DOI: 10.1111/j.1600-051x.2005.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of environmental factors – tobacco smoking

Abstract: Tobacco smoking has widespread systemic effects, many of which may provide mechanisms for the increased susceptibility to periodontitis and the poorer response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
474
2
33

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 433 publications
(526 citation statements)
references
References 174 publications
(202 reference statements)
17
474
2
33
Order By: Relevance
“…The balance between destructive cytokines such as IL-1a, IL-1b, TNFa, IL6, IL8 and prostaglandins and protective cytokines such as TGF-b, IGF and interferons shifts more towards destructive profile in smokers. Also it has been speculated that the interference of smoking with inflammatory signs and symptoms is mediated by vasoconstructive effects of nicotine [2,3,[19][20][21]. The present study has observed that smokers with chronic periodontitis exhibit more clinical periodontal damage and relatively higher oxidative stress compared to non-smokers with chronic periodontitis.…”
Section: Discussionsupporting
confidence: 52%
“…The balance between destructive cytokines such as IL-1a, IL-1b, TNFa, IL6, IL8 and prostaglandins and protective cytokines such as TGF-b, IGF and interferons shifts more towards destructive profile in smokers. Also it has been speculated that the interference of smoking with inflammatory signs and symptoms is mediated by vasoconstructive effects of nicotine [2,3,[19][20][21]. The present study has observed that smokers with chronic periodontitis exhibit more clinical periodontal damage and relatively higher oxidative stress compared to non-smokers with chronic periodontitis.…”
Section: Discussionsupporting
confidence: 52%
“…The mechanism by which smoking affects periodontal plastic surgery outcomes remains unclear (10), but smoking interferes with several physiological mechanisms and cellular functions (16). The large number of tobacco toxins may impair periodontal healing (3).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, current smokers showed a higher trend for having impacts on their OHQoL compared to former smokers and never smokers; however this difference was not significant. The negative effect of smoking on OHQoL is probably due to the harmful effects of smoking on oral tissues (26).…”
Section: Discussionmentioning
confidence: 99%